OSTATNIE MIESIĄCE. UWAGI O SYTUACJI W PZPR PO WYBORACH W CZERWCU 1989 ROKU - Jabłonowski, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the political system of Peoples’ Republic of Poland, Polish United Workers’ Party (PZPR) for more than four decades has played a key role in all areas of country’s policy. In the end of the 80’s, as a result of changes in Poland, fractures within the Party deepened. They were a result of differences in understanding of the requirements for, the scale and pace of reforms both in the party and the country. The article follows the last few months of functioning of PZPR when, after the June ’89 elections, a deep division within the party took place. Consequently it has been dissolved during the 11th Congress, fated by, inter alia, crisis of confidence in own arguments, strength and own leaders. This moment is a major key in the process of destruction of political system, that has been functioning in Poland since 1940’s.